Impact of blending for direct potable reuse on premise plumbing microbial ecology and regrowth of opportunistic pathogens and antibiotic resistant bacteria. (15th March 2019) - Garner, Emily; Inyang, Mandu; Garvey, Elisa; Parks, Jeffrey; Glover, Caitlin; Grimaldi, Assumption; Dickenson, Eric; Sutherland, Justin; Salveson, Andrew; Edwards, Marc A.; Pruden, Amy
Abstract: Little is known about how introducing recycled water intended for direct potable reuse (DPR) into distribution systems and premise plumbing will affect water quality at the point of use, particularly with respect to effects on microbial communities and regrowth. The examination of potential growth of opportunistic pathogens (OPs) and spread of antibiotic resistance genes (ARGs), each representing serious and growing public health concerns, by introducing DPR water has not previously been evaluated. In this study, the impact of blending purified DPR water with traditional drinking water sources was investigated with respect to treatment techniques, blending location, and blending ratio. Water from four U.S. utility partners was treated in bench- and pilot-scale treatment trains to simulate DPR with blending. Water was incubated in simulated premise plumbing rigs made of PVC pipe containing brass coupons to measure regrowth of total bacteria (16S rRNA genes, heterotrophic plate count), OPs ( Legionella spp., Mycobacterium spp., Pseudomonas aeruginosa ), ARGs ( qnr A, van A), and an indicator of horizontal gene transfer and multi-drug resistance ( int I1). The microbial community composition was profiled and the resistome (i.e., all ARGs present) was characterized in select samples using next generation sequencing. While regrowth of total bacteria (16S rRNA genes) from the start of the incubation through week eight consistently occurred across tested scenarios (Wilcoxon, p ≤ 0.0001), total bacteria were not more abundant in the water or biofilm of any DPR scenario than in the corresponding conventional potable condition (p ≥ 0.0748). Regrowth of OP marker genes, qnr A, van A, and int I1 were not significantly greater in water or biofilm for any DPR blends treated with advanced oxidation compared to corresponding potable water (p ≥ 0.1047). This study of initial bacteria colonizing pipes after introduction of blended DPR water revealed little evidence (i.e., one target in one water type) of exacerbated regrowth of total bacteria, OPs, or ARGs in premise plumbing. Graphical abstract: Image 1 Highlights: Total bacterial regrowth in direct potable reuse (DPR) comparable to potable water. No significant difference in Legionella occurrence in DPR versus potable water. Mycobacterium regrowth was greater in one utility's reuse water than potable water. No difference in qnr A, van A, or int I1 occurrence in DPR versus potable water. Appropriate DPR treatment train and optimal blend ratio limits bacterial regrowth.